Sociocultural Factors Influencing Human Streptococcus suis Disease in Southeast Asia - Anusak Kerdsin; Mariela Segura; Nahuel Fittipaldi; Marcelo Gottschalk (Foods, 2022)
The public health systems of Southeast Asian countries are financially challenged by a comparatively higher incidence of human S. suis infections than other geographical areas. Efforts to improve practices in production settings, including improved meat inspection regulations, prevention of the slaughtering of non-healthy pigs, and enhanced hygiene practices at processing facilities, along with improvements in the pork supply chain, all appear promising for reducing food cross-contamination with S. suis. However, opportunities for intervention at the societal level are also needed to effect changes, as population behaviors such as the consumption of raw pork, blood, and offal products are important contributors to the increased incidence of human S. suis disease in Southeast Asia. A plethora of factors are associated with the consumption of these high-risk dishes, including traditional culture and knowledge, shared beliefs, socio-economic level, and personal attitudes associated with gender and/or marital status. Education and intervention in behavioral attitudes that are sensible to cultural practices and traditions may provide additional means to reduce the burden of S. suis human disease in Southeast Asia.